Polymerase chain reaction for detection of Kaposi’s sarcoma virus in breast tumors - Ghane, Masood; Eghbali, Mina (Archives of Advances in Biosciences, 2015)
Human Herpes Virus 8 (HHV8) causes Kaposi’s sarcoma, a common cancer among AIDS patients. It is proposed that this virus plays a role in formation of some blood vessel and lymphoma tumors. This study aimed to investigate the frequency of KSHV among benign and malignant breast tumors. A total of 24 carcinomas and 24 fibroadenomas paraffin embedded tumoral tissue samples were obtained from the pathology sections of Toos and Firoozgar hospitals in Tehran, Iran. All samples had been collected from patients during a period of time effective from June 2013 to February 2014. DNA was extracted from all samples and their infection with HHV8 was examined by PCR technique. The results obtained by this study showed that 6 out of 24 carcinoma samples (25%) were infected by KSHV, while the number of fibroadenoma samples infected by this virus was 9 (37.5%). The frequency of HHV8 infection was different among malignant and benign tumors. Based on the results obtained by this study, KSHV was observed in both benign and malignant tumors. Since KSHV was observed in both types of tumors therefore, it may not have significant relationship with tumor type. The role of KSHV in vessel tumors has been proved by many studies during the past decade. Some other studies have also defined a role for this virus in formation of breast fibroadenoma tumor. Therefore, further studies are needed to define the influence of this virus in breast tumors formation.